Preparticipation screening of young competitive athletes for cardiovascular disorders - Chandra, N.; Papadakis, M.; Sharma, S. (The Physician and Sportsmedicine, 2010)
The beneficial effects of regular physical exercise on cardiovascular morbidity and mortality are well documented. In rare cases, however, athletes with cardiovascular abnormalities are at increased risk of exercise-related sudden cardiac death (SCD). Paradoxically, most SCDs can be attributed to cardiovascular abnormalities that can be identified during an athlete`s life. Such abnormalities can be minimized by several therapeutic strategies, including insertion of an implantable cardioverter-defibrillator. Based on these considerations, the medical and sporting governing bodies recommend preparticipation cardiovascular screening (PPS) in young competitive athletes (aged = 35 years) to identify potentially fatal cardiovascular disorders. However, PPS is associated with several controversies related to the efficacy, cost-effectiveness, and impact of false-positive results. This article aims to provide a detailed overview of the issues concerning PPS based on current evidence.